2007
DOI: 10.1104/pp.107.101733
|View full text |Cite
|
Sign up to set email alerts
|

A Bacterial Transgene for Catalase Protects Translation of D1 Protein during Exposure of Salt-Stressed Tobacco Leaves to Strong Light

Abstract: During photoinhibition of photosystem II (PSII) in cyanobacteria, salt stress inhibits the repair of photodamaged PSII and, in particular, the synthesis of the D1 protein (D1). We investigated the effects of salt stress on the repair of PSII and the synthesis of D1 in wild-type tobacco (Nicotiana tabacum 'Xanthi') and in transformed plants that harbored the katE gene for catalase from Escherichia coli. Salt stress due to NaCl enhanced the photoinhibition of PSII in leaf discs from both wild-type and katEtransf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(40 citation statements)
references
References 40 publications
0
40
0
Order By: Relevance
“…The PsbO content in isolated thylakoids, however, decreased. Recent reports show that the eVects of salt stress on higher plants and cyanobacteria are due to the generation of reactive oxygen species, which aVects both the reduced and the oxidized sites of PSII (Al-Taweel et al 2007;Takahashi and Murata 2008). Allakhverdiev et al (2000) reported that, in addition to PSII, PSI is equally inactivated by osmotic stress-the present study is focused on further exploring the role of PSI damage in salt stress.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The PsbO content in isolated thylakoids, however, decreased. Recent reports show that the eVects of salt stress on higher plants and cyanobacteria are due to the generation of reactive oxygen species, which aVects both the reduced and the oxidized sites of PSII (Al-Taweel et al 2007;Takahashi and Murata 2008). Allakhverdiev et al (2000) reported that, in addition to PSII, PSI is equally inactivated by osmotic stress-the present study is focused on further exploring the role of PSI damage in salt stress.…”
Section: Introductionmentioning
confidence: 95%
“…In some reports, the eVects of salt stress on PSII were due to the dissociation of the 23-kDa polypeptide extrinsically bound to PSII (Murata et al 1992). Salt stress has also been reported to reduce D 1 protein turnover in both cyanobacteria and plants (Al-Taweel et al 2007;Allakhverdiev and Murata 2008).…”
Section: Introductionmentioning
confidence: 97%
“…It has been reported that engineering a single gene encoding antioxidant enzymes (SOD, CAT or POX) can enhance the tolerance to salt stress (Al-Taweel et al 2007;Badawi et al 2004;Tanaka et al 1999), while some researches showed that transformation of a gene encoding antioxidant enzymes could not confer salt tolerance (Katsuhara et al 2005;Light et al 2005;Tseng et al 2007;Zhang et al 2000). These controversial conclusions imply that the differences in salt tolerance may not necessarily be the consequence of the different activities of these antioxidant enzymes (SOD, CAT and POX), and such speculation has been confirmed by the fact that higher antioxidant enzyme activities have been observed in saltsensitive cultivars, but were associated with higher ROS level (Mandhania et al 2006;Neto et al 2006;Rahnama and Ebrahimzadeh 2005).…”
Section: Introductionmentioning
confidence: 99%
“…50 During salt or drought stress, synthesis of proteins involved in PSII repair is affected leading to photoinhibition. [51][52][53] GB antagonizes the inhibition of protein biosynthesis 69 and Artiplex. 42 betA, E. coli gene encoding choline dehydrogenase.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…55 Therefore, GB can provide tolerance to abiotic stresses even at low concentration by protecting photosynthesis under abiotic stress. 15,51,53,54 Tolerance to abiotic stress is coupled with contribution of endogenous genes in transgenic plants. The proposed mechanisms for GB-mediated abiotic stress tolerance include stabilization of native structure of proteins and enzymes, osmoregulation, membrane integrity, protection of photosynthesis and detoxification of reactive oxygen radicals produced during stress ( Table 1).…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%